MODEL SPASIAL STATISTIK KEPEMILIKAN SEPEDA MOTOR DI KECAMATAN BANYUMANIK, KOTA SEMARANG - Shepta Yudha Ardiansyah; Anita Ratnasari Rakhmatullah (Department of Urban and Regional Planning, Diponegoro University, 2014)
Semarang is a fast forward and fast growing city viewed from its economic growth. However, the increased population along by increased activity gives a new difficulty, that is congestion. The existence of urbanization encourages people tend to prefer a suburban area to the center of the city. With the growing movement of transportation activity, it has pushed the level of ownership of private vehicles, especially motorcycles in the suburbs. Banyumanik Sub-district as a suburb of the Semarang City is functioned as settlements development direction. Banyumanik Sub-district is the highest number of motorcycle ownership in Semarang sub urban with the amount of 20.428 units. For understanding the motorcycle ownership concentration, it is required the study of distribution and spatial aspects, so that it can be seen spreading evenly or not. The method used in this research is quantitative descriptive and spatial modeling approach named Spatial Statistics Analysis using GIS (Geographic Information System). According to the research results, it is revealed that the movement system of the motorcycle user community in Banyumanik Sub-district reaches until 37% toward the center of the city, 58% Banyumanik stir around the area, and a 5% move toward Semarang regency. As a results of the analysis of spatial patterns, it is showed that the distribution of the motorcycles ownership forms a cluster pattern with a high concentration level (High Cluster). The highest concentrations of motorcycle ownership exist in the surrounding of Banyumanik Sub-district, while the lowest ownership concentration is in the region such as the Bukitsari Residence, and Graha Estetika Residence